Miasthenia Gravis Pada Laki-Laki 60 Tahun dengan Community Acquired Pneumonia : Laporan Kasus - Fitriyani, Fitriyani; Nur Azizah, Nabilah (Medula, 2024)
Myasthenia gravis is an autoimmune disease involving the neuromuscular junction (NMJ) of skeletal muscles. It clinically manifests as muscle weakness that worsens with activity or fatigue and improves after rest. It typically involves muscles of the eyes, throat, and extremities. The global epidemiology of myasthenia gravis (MG) affects 30 per 1 million people per year, with an incidence rate of 20 per 100,000 population. In men, the disease often occurs at the age of 60 years. Various conditions can trigger it such as infections, immunizations, surgeries, and medications. Pneumonia is a serious form of acute lower respiratory tract infection in lung parenchyma, encountered in about 15-20% of cases. Case: A 60-year-old male patient presented with complaints of shortness of breath, difficulty swallowing, difficulty opening eyelids, and productive cough. From the history, physical examination, and diagnostic tests, the diagnosis of myasthenia gravis and community-acquired pneumonia was established. The patient received therapy with pyridostigmine bromide 5 x 60mg, methylprednisolone injection 125mg every 12 hours, and levofloxacin injection 750mg every 24 hours.